Researching EFL Students' Disengagement in an Online Content-Teaching Classroom - Candra Dewi Dwika Wardani; Yustinus Calvin Gai Mali (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
Research proves that students’ engagement becomes an important role in the teaching and learning process in English as a Foreign Language (EFL) classroom. However, due to the COVID-19 pandemic, the teaching and learning process had to be conducted online with its restrictions such as the limitation of doing face-to-face communication and the technological issue. Referring to those limitations, students’ disengagement is more likely to increase in online classroom setting. As based on Egbert’s (2021) task-engagement principles, this study explores factors that cause students’ learning disengagement in a Teaching English for Adult Learners (TEAL) class, especially during lecturers’ presentation sessions that were conducted through the Zoom application. To achieve the research goal, a total of seven (7) TEAL students in an English Language Education Program (ELEP) at a private university in Central Java, Indonesia were involved in this study. To collect the data, a semi-structured interview was used as the research instrument. Through a thematic analysis on the interview transcripts, the researcher revealed three main factors that caused students’ disengagement: social interaction, learning support, and task difficulty. Each of these factors were discussed and placed in the discourse of the engagement-related literature. At the end of the paper, the researcher presented practical recommendations for language teachers teaching in a similar context to improve their EFL student’s learning engagement and ideas for future research.